Selective Government Interventions and Economic Growth : A Survey of the Asian Experience and its Applicability to New Zealand - Ostry, Jonathan (IMF Policy Discussion Papers; Policy Discussion Paper, 1993)
Since the mid-1980s, New Zealand has been engaged in a broad-ranging economic reform program--involving liberalization of key sectors of the economy, reduction in trade protection, and trimming of the public sector--in order to restructure its economy and stimulate growth. With growth performance having been rather lackluster in recent years, questions have been raised as to whether a more interventionist approach--such as that followed by some Asian countries--might be warranted in order to place the economy on a higher growth path. A review of the empirical literature dealing with the experience of the dynamic Asian economies does not suggest that their success can be attributed to any significant degree to selective government interventions.